Census Study of Ducks, Swans and Geese from High-Altitude Wetlands of Pakistan - Nazir, Fakhra; Malik, Inayatullah; Shah, Safdar Ali (CORE Scholar, 2018)
The family Anatidae consists of aquatic birds such as ducks, geese and swans of varied sizes that belong to the order Anseriformes (Carboneras, 1992). The Anatidae comprise of approximately 148 species (Johnsgard, 2010). This family is commonly found across the globe except for in Antarctica. Data on ecology and population of these water birds was taken from protected areas of Pir Lasura National Park (June-July 2009), Banjosa Game Reserve (May-June 2009), Dhirkot National Park (February 2008), Pir Chanasi National park (April-May 2010) and Tolipir National Park (April-May 2008). Only four species from the family Anatidae were found in the study region. Banjosa Game Reserve had the most diversity with 41 % of Mute swan, 10% of Lesser White-fronted Goose and 32% of the Northern Shoveler. Efforts are needed by the concerned parties to conserve the population of the Lesser White-fronted Goose which was only observed in Banjosa Game Reserve and had a low population density, along with a vulnerable status globally.